Morphosyntactic core features of Kivu Swahili: A synopsis - Bose, Paulin Baraka; Nassenstein, Nico (AAeO - Afrikanistik-Aegyptologie-Online, 2016)
This paper aims to summarize the most salient features of Kivu Swahili, the variety of Kiswahili spoken in the Kivu provinces of DR Congo. It addresses the core differences between ECS (Kiswahili as spoken on the Tanzanian coast) and the Swahili from Goma/Bukavu, also taking into consideration contact-induced change and speakers’ free variations. The paper aims to illustrate the complex morphosyntax of the language, and questions the general description of the variety as a ‘pidginized’ or ‘simplified’ form of Kiswahili, due to its divergence from ECS and the peripheral location of the community of speakers. Moreover, the paper aims to address speakers’ acrolectal reference to the standard variety, and discusses this latter against a theoretical background of the ‘constructedness’ of East Coast Swahili. Some concluding remarks summarize the salient features of Kivu Swahili, and suggest perspectives on more in-depth analyses of the language.